Interrogating the genetic profile of sporadic colorectal cancer - Fadhil, Wakkas M. (2019)
Background and aims: Colorectal cancer (CRC) is one of the most common types of cancers. Prognosis for CRC is dependent on the stage of the disease at diagnosis and a variety of molecular features including expression of biomarkers and gene mutation. This study sought to (i) develop molecular tests for use in molecular profiling of formalin-fixed paraffin embedded tissue (FFPE) and (ii) interrogate the molecular profile and biomarker expression in multiple cohorts of sporadic CRC.